2004
DOI: 10.1097/00006982-200402000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Full-Thickness Retina in the Rhodopsin Transgenic Pig

Abstract: Full-thickness neuroretinal grafts can be transplanted to a large animal host with photoreceptor degeneration. The transplantation procedure is relatively atraumatic to both graft and host tissue, and the grafts survive well for at least 4 months. The graft and host retina does not seem to form extensive neuronal contacts, and future work must be directed at stimulating such activity without disrupting the retinal neuronal organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 11 publications
3
33
0
1
Order By: Relevance
“…Additionally, most of the inner retinal layers were seen in the grafts which was somewhat surprising. We previously reported that neonatal full-thickness grafts to normal and degenerating hosts do not develop inner layers [15,16], a phenomenon best explained by the separation from its retinal blood supply [18]. The blood vessels found in all grafts in the present study, indicate that fetal full-thickness grafts can develop a new inherent retinal circulation and thereby also form inner layers.…”
Section: Transplant Survival and Developmentsupporting
confidence: 53%
See 4 more Smart Citations
“…Additionally, most of the inner retinal layers were seen in the grafts which was somewhat surprising. We previously reported that neonatal full-thickness grafts to normal and degenerating hosts do not develop inner layers [15,16], a phenomenon best explained by the separation from its retinal blood supply [18]. The blood vessels found in all grafts in the present study, indicate that fetal full-thickness grafts can develop a new inherent retinal circulation and thereby also form inner layers.…”
Section: Transplant Survival and Developmentsupporting
confidence: 53%
“…The surgical procedures were, with a few exceptions, identical to the one reported in a previous paper [16], and will only be summarized here. Six consecutive animals were operated in 2 sessions of 3 animals each.…”
Section: Surgical Proceduresmentioning
confidence: 95%
See 3 more Smart Citations